Ali bin Abi Thalib: Kekhalifahan di Tengah Tiga Pemberontakan Besar - Nur Hasanah Hasibuan; Afrizal Afrizal; Sawaluddin Sawaluddin (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to examine the three major rebellions faced by Ali ibn Abi Talib during his leadership: the Rebellion of Talhah and his allies, the Challenge of the Khawarij, and the Rebellion of Mu'awiyah. These events had a profound impact on early Islamic politics and theology. This research utilizes a qualitative method with a descriptive-analytical approach, focusing on a literature review of primary and secondary sources. Data were gathered through in-depth analysis of various academic journals discussing the dynamics of Ali's leadership. The findings reveal that these three rebellions not only weakened Ali’s political power but also exacerbated divisions within the Muslim community, especially concerning theological and leadership issues. These conflicts triggered the emergence of various Islamic sects, such as the Khawarij and Shia, which continue to influence Islamic political development in subsequent periods. The conclusion of this study is that Ali ibn Abi Talib’s leadership period marked a significant transitional era in Islamic history, during which major shifts in politics and theology had long-lasting effects on the Muslim community.